2022
DOI: 10.3389/fcvm.2022.858889
|View full text |Cite
|
Sign up to set email alerts
|

The U-Shaped Relationship Between Serum Uric Acid and Long-Term All-Cause Mortality in Coronary Artery Disease Patients: A Cohort Study of 33,034 Patients

Abstract: BackgroundAssociations between high serum uric acid (SUA) and cardiovascular diseases have been reported. However, few studies have been conducted to explore the relationship between SUA and long-term all-cause mortality in coronary artery disease (CAD) patients. Our study aims to investigate the relationship between SUA and long-term all-cause mortality in patients with CAD.MethodsFrom January 2007 to December 2018, we divided 33,034 patients with CAD admitted in the Guangdong Provincial People's Hospital int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…It should be noted, however, that although these studies have confirmed a U-shaped relationship between SUA and all-cause mortality, the authors reported different optimal thresholds for SUA. For example, Weicheng et al found that in an older population aged >65 years, both low (<4 mg/dl) and high (>8 mg/dl) SUA levels were independently associated with an increased risk of all-cause mortality ( 19 ), and similarly in a cohort study of a Chinese population with coronary artery disease, the authors identified a U-shaped association in which the risk of all-cause mortality increased at both low (≤5.05 mg/dl) and high (≥8.0 mg/dl) levels of SUA ( 18 ). In addition, a cohort study including 375,163 Korean general medical examination population found that both low uric acid group (<3.5 mg/dl in men; <2.5 mg/dl in women) and high uric acid group (>9.5 mg/dl in men; >8.5 mg/dl in women) increased all-cause mortality compared to the sex-specific reference group ( 22 ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It should be noted, however, that although these studies have confirmed a U-shaped relationship between SUA and all-cause mortality, the authors reported different optimal thresholds for SUA. For example, Weicheng et al found that in an older population aged >65 years, both low (<4 mg/dl) and high (>8 mg/dl) SUA levels were independently associated with an increased risk of all-cause mortality ( 19 ), and similarly in a cohort study of a Chinese population with coronary artery disease, the authors identified a U-shaped association in which the risk of all-cause mortality increased at both low (≤5.05 mg/dl) and high (≥8.0 mg/dl) levels of SUA ( 18 ). In addition, a cohort study including 375,163 Korean general medical examination population found that both low uric acid group (<3.5 mg/dl in men; <2.5 mg/dl in women) and high uric acid group (>9.5 mg/dl in men; >8.5 mg/dl in women) increased all-cause mortality compared to the sex-specific reference group ( 22 ).…”
Section: Discussionmentioning
confidence: 86%
“…A recent review of studies conducted on populations with different health conditions ( 9 ), including healthy individuals ( 16 , 17 ), patients with coronary heart disease ( 18 ), older patients ( 19 ), patients with hypertension ( 20 ), and patients with chronic kidney disease ( 21 ), summarized the U-shaped association between SUA and various adverse clinical outcomes, such as all-cause mortality and cardiovascular mortality. Our study confirmed the U-shaped relationship between SUA and all-cause mortality in patients with hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study concluded that blood uric acid level reached a minimum risk of all-cause mortality in patients with CAD at 6.52 mg/dL in men and 5.83 mg/dL in women, with a subsequent increase in the risk of mortality regardless of whether uric acid concentrations increased or decreased. The results of the study showed that CAD with serum uric acid level in the interval (5.59 mg/dL ≤ SUA < 6.8 mg/dL) had a better prognosis [ 93 ]. However, the result of the EPOCH-JAPAN study differed, with low uric acid levels (<4.6 mg/dL in men and <3.9 mg/dL in women) increasing mortality from CAD, heart failure, and stroke [ 90 ].…”
Section: Uric Acid Metabolismmentioning
confidence: 99%
“…Is it the drug or the uric acid concentration that makes uric acid-lowering therapy effective in reducing the risk of poor prognosis in CAD, given its effect on improving the risk of poor prognosis in CAD? Clinical studies have shown a U-shaped relationship between serum uric acid and all-cause mortality in CAD in the group using uric acid-lowering drugs, with low and high levels of serum uric acid still associated with increased long-term all-cause mortality in patients with CAD, and the use of uric acid-lowering drugs did not reduce all-cause mortality [ 93 ]. Based on the available studies, it is believed that there are harmful effects of uric acid-lowering drugs that increase the risk of death from CAD and that a sharp decrease in uric acid concentration may be responsible for the harmful effects of uric acid-lowering drugs [ 110 , 111 ].…”
Section: Uric Acid Metabolismmentioning
confidence: 99%